COMPARATIVE STUDY OF SERUM CREATININE IN PATIENTS GOING THROUGH HEMODIALYSIS WITH OR WITHOUT HEPATITIS C INFECTION (Journal of Medical & Health Sciences Review, 2025)
The most frequent cause of chronic viral liver disease in hemodialysis patients is hepatitis C. Hemodialysis patients continue to have a high prevalence of chronic Hepatitis C Virus (HCV) infection, which is a serious public health issue. Comparing serum creatinine levels in hemodialysis patients with and without HCV infection was the main goal of this study. From March to June 2023, a four-month cross-sectional study was carried out. Patients receiving hemodialysis at different dialysis facilities throughout Lahore had their blood samples taken. Alkhidmat Lab in Lahore handled the processing and analysis of these samples. Long-term dialysis patients were tested for the presence of HCV using the Enzyme-Linked Immunosorbent Assay (ELISA). 102 samples in all were analyzed. Of these, 63 patients had negative HCV tests and 39 had positive ones. A significant correlation between HCV infection and elevated serum creatinine levels in hemodialysis patients was found by statistical analysis, with a p-value of less than 0.05. Additionally, the data revealed that male patients had a higher prevalence of HCV infection (61.2%) than female patients (38.8%). According to the study's findings, patients undergoing long-term hemodialysis are still at serious risk from Hepatitis C. Additionally, the strong link between HCV infection and changed creatinine levels emphasizes the necessity of ongoing observation and early detection techniques to enhance patient outcomes and lessen the burden of disease in this susceptible group.